Intelligent Systems and Applications Proceedings of the 2018 Intelligent Systems Conference (IntelliSys) Volume 1 - Arai, Kohei; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Gathering the Proceedings of the 2018 Intelligent Systems Conference (IntelliSys 2018), this book offers a remarkable collection of chapters covering a wide range of topics in intelligent systems and computing, and their real-world applications. The Conference attracted a total of 568 submissions from pioneering researchers, scientists, industrial engineers, and students from all around the world. These submissions underwent a double-blind peer review process, after which 194 (including 13 poster papers) were selected to be included in these proceedings. As intelligent systems continue to replace and sometimes outperform human intelligence in decision-making processes, they have made it possible to tackle many problems more effectively. This branching out of computational intelligence in several directions, and the use of intelligent systems in everyday applications, have created the need for such an international conference, which serves as a venue for reporting on cutting-edge innovations and developments. This book collects both theory and application-based chapters on all aspects of artificial intelligence, from classical to intelligent scope. Readers are sure to find the book both interesting and valuable, as it presents state-of-the-art intelligent methods and techniques for solving real-world problems, along with a vision of future research directions.
ViZDoom: DRQN with Prioritized Experience Replay, Double-Q Learning and Snapshot Ensembling -- Ship Classification from SAR Images based on Deep Learning -- HIMALIA: Recovering Compiler Optimization Levels from Binaries by Deep Learning -- Architecture of Management Game for Reinforced Deep Learning -- The Cognitive Packet Network with QoS and Cybersecurity Deep Learning Clusters -- Convolution Neural Network Application for Road Asset Detection and Classification in LiDAR Point Cloud -- PerceptionNet: A Deep Convolutional Neural Network for Late Sensor Fusion -- Reinforcement Learning for Fair Dynamic Pricing -- A Classification-Regression Deep Learning Model for People Counting -- The Impact of Replacing Complex Hand-Crafted Features with Standard Features for Melanoma Classification using Both Hand-Crafted and Deep Features -- Deep Learning in Classifying Depth of Anesthesia (DoA) -- Content based Video Retrieval using Convolutional Neural Network -- Proposal and Evaluation of an Indirect Reward Assignment Method for Reinforcement Learning by Profit Sharing Method -- Eye-Tracking to Enhance Usability: A Race Game -- Eye-Tracking to Enhance Usability: A Race Game -- Automatized Approach to Assessment of Degree of Delamination around a Scribe -- Face Detection and Recognition for Automatic Attendance System -- Fine Localization of Complex Components for Bin Picking -- Intrusion Detection in Computer Networks based on KNN, K-Means++ and J48 -- Cooperating with Avatars through Gesture, Language and Action -- A Safer YouTube Kids: An Extra Layer of Content Filtering using Automated Multimodal Analysis -- Designing an Augmented Reality Multimodal Interface for 6DOF Manipulation Techniques -- InstaSent: A Novel Framework for Sentiment Analysis based on Instagram Selfies -- Segmentation of Heart Sound by Clustering using Spectral and Temporal Features -- Evaluation of Classifiers for Emotion Detection while Performing Physical and Visual Tasks: Tower of Hanoi and IAPS -- Investigating Input Protocols, Image Analysis, and Machine Learning Methods for an Intelligent Identification System of Fusarium Oxysporum Sp. in Soil Samples -- Intelligent System Design for Massive Collection and Recognition of Faces in Integrated Control Centres -- Wheat Plots Segmentation for Experimental Agricultural Field from Visible and Multispectral UAV Imaging -- Evaluation of Image Spatial Resolution for Machine Learning Mapping of Wildland Fire Effects -- Region-based Poisson Blending for Image Repairing -- Modified Radial Basis Function and Orthogonal Bipolar Vector for Better Performance of Pattern Recognition -- Video Detection for Dynamic Fire Texture by using Motion Pattern Recognition -- A Gaussian-Median Filter for Moving Objects Segmentation Applied for Static Scenarios -- Straight Boundary Detection Algorithm based on Orientation Filter -- Using Motion Detection and Facial Recognition to Secure Places of High Security: A Case Study at Banking Vaults of Ghana -- Kinect-Based Frontal View Gait Recognition using Support Vector Machine -- Curve Evolution based on Edge Following Algorithm for Medical Image Segmentation -- Enhancing Translation from English to Arabic using Two-Phase Decoder Translation -- On Character vs Word Embeddings as Input for English Sentence Classification.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Artificial intelligence; Computational Intelligence; Control, Robotics, Automation; Artificial Intelligence